Tourism effects of pandemics: New insights from novel coronavirus - E. Osuji; O. Evans (SPOUDAI - Journal of Economics and Business, 2020)
This study investigates the effect of coronavirus on tourism worldwide using data on confirmed cases of coronavirus by European Centre for Disease Prevention and Control [ECDCPC] and Google trends data. The analysis uses a variety of estimation approaches, including quantile regressions and causality tests. The study showed that cases of coronavirus have a negative relationship with tourism. In general, increasing cases of coronavirus would tend to reduce travel to tourist destinations. More interestingly, the effects are heterogeneous across the distribution of cases of coronavirus.
Keywords: Z30; Z31; L18; 330; Travel; tourism; pandemics; coronavirus